Outcome of superficial brachial axial pattern flaps used to close skin defects in dogs: 16 cases (1996‐2019). (27th October 2021) - Villedieu, E.; Nolff, M. C.; Del Magno, S.; Emmerson, T.; Field, E.; Hattersley, R.; De La Puerta, B.; Ragni, R. A.; Baines, S. J.
Abstract : Objectives: To report the complication rate, type of complications and outcome of the superficial brachial axial pattern flap when used for closure of skin defects in dogs. Materials and Methods: Medical records of dogs treated with a superficial brachial axial pattern flap for closure of a skin defect were reviewed. Information regarding signalment, reason for axial pattern flap use, skin flap size, flap healing, postoperative complications and need for revision surgery was collected. Results: Sixteen dogs were included in the study. Indications for the superficial brachial axial pattern flap included closure following tumour removal (15/16, 94%) and management of a non‐healing wound on the olecranon (1/16, 6%). Postoperative complications occurred in all dogs and included partial dehiscence (7/16, 44%), partial flap necrosis (6/16. 38%), seroma formation (5/16, 31%), flap oedema (3/16, 19%) and complete flap necrosis (2/16, 13%). Eight flaps (50%) healed without open wound management or additional surgery. Five dogs required open wound management without additional surgery, and three dogs (19%) required revision surgery. Clinical Significance: Use of the superficial brachial axial pattern flap was associated with a high rate of complications. Most complications were managed without additional surgery and all wounds eventually healed, in some cases after prolonged open wound management.